c Gossip Girl novel - Ziegesar, Cecily Von. (b, 2007)
The Gossip Girl and her friends spend a summer partying before heading off to college in the fall.
Keywords: Teenagers -- Juvenile fiction. -- New York (State) -- New York; Gossip -- Juvenile fiction. -- New York (State) -- New York; High school students -- Juvenile fiction. -- Fiction. -- New York (State) -- New York